Manner of death of older people with regard to blood alcohol concentration - Juríčková, Lubica; Ivanová, K; Dobiáš, Martin; Andrášik, Richard; Ondra, Peter (Central European Journal of Public Health, 2017)
OBJECTIVE: Alcohol abuse is related to a wide variety of negative health outcomes including mortality in older people. Alcohol abuse in older people is characterised by certain specific features uncommon in general adult population. The main objective of this study was to analyse the autopsy protocols of deceased older people in relation to blood alcohol concentration (BAC), sex, age, and manner of death. As a positive BAC, >0.20 g/kg was accepted. METHODS: The sample consists of 1,012 deceased older people (i.e. aged 65 years and over) selected out of 2,377 autopsied subjects in the period from 2003–2013. Subjects included into the sample were chosen via the proportional sampling method. Data (BAC, sex, age, and manner of death) was recorded in a single structured protocol. Data was evaluated statistically (Kolmogorov-Smirnov two-sample test, Wilcoxon two-sample test, risk ratio). RESULTS: Among older people, there has been a statistically significant correlation of natural death with sex (men died earlier) and with increased BAC (people with positive BAC died earlier). In case of violent death there is a difference in the types of accidents in older people with positive BAC (>0.2 g/kg) and with negative BAC (≤0.2 g/kg). Drowning is more common in older people with positive BAC. CONCLUSIONS: Health campaigns in Europe and the Czech Republic aimed at reducing alcohol consumption mainly deal with young people. Alcohol abuse has an impact on premature mortality even in older people. As shown by this study, older people with positive BAC die significantly earlier.
Keywords: Female; Age Factors; Cause of Death; Geriatric Assessment; ženské pohlaví; Blood Alcohol Content; věkové faktory; lidé; alkoholismus; Aged, 80 and over; geriatrické hodnocení; Alcoholism; Sex Factors; retrospektivní studie; Male; Aged; sexuální faktory; Czech Republic; Česká republika; senioři nad 80 let; senioři; mužské pohlaví; příčina smrti; Retrospective Studies; obsah alkoholu v krvi; Humans